RANCANG BANGUN APLIKASI SURVEY KEPUASAN PELANGGAN BERBASIS WEB PADA PT. UWAIS GROUP BERKARYA MENGGUNAKAN METODE PROTOTYPING - Aditia; Muhamad Hanafi; Muhammad Rio Arya Pratama; Saprudin (Jurnal Riset Informatika dan Inovasi, 2023)
Abstrak− PT. Uwais Group Berkarya is a company engaged in the health sector. As a company that focuses on customer service, PT. Uwais Group Berkarya needs to ensure customer satisfaction in order to maintain and improve the quality of services provided. To measure the level of customer satisfaction, PT. Uwais Group Berkarya decided to make a customer satisfaction survey application. This application will enable companies to obtain feedback from customers quickly and effectively. Thus, PT. Uwais Group Berkarya can find out what customers want and identify areas that need improvement. In designing and developing a customer satisfaction survey application, PT. Uwais Group Berkarya decided to use the prototyping method. This method was chosen because it allows companies to create a prototype model of the application before making the final version. Thus, PT. Uwais Group can identify problems and improvements that need to be made to applications before marketing them to customers. Through a customer satisfaction survey application built using the prototyping method, PT. Uwais Group Berkarya is expected to be able to obtain more accurate and valid data regarding customer satisfaction. In addition, with this customer satisfaction survey application, companies can also improve interaction and communication with customers, so that it can help improve service quality and overall customer satisfaction. The methodology used by the author in designing this library repository application is the prototyping method. PT services Uwais Group Berkarya. By identifying low levels of customer satisfaction, readers can understand that customer satisfaction surveys are an effective way to find out customer needs and expectations, so that more targeted improvements and service improvements can be made. 2. Remembering how important it is to use effective survey methods in collecting accurate data and describing overall customer satisfaction. With the application made, it can be used as evaluation material for PT. Uwais Group Work to improve service performance and find out the results of performance and the extent to which the level of community satisfaction with the services that have been provided and can measure the performance of PT. Uwais Group Berkarya is based on the criteria for questions about the services performed on it. Keywords: Customer Service, Customer Satisfaction Survey, Information Systems.